Epidemiological characteristics and trends of hand-foot-mouth disease in Shanghai, China from 2011 to 2021 - Wang, Jing; Zhang, Shan (Frontiers in Public Health, 2023)
Hand, foot and mouth disease (HFMD) is a kind of infectious disease caused by enterovirus infection. In this study we analysed the epidemiological characteristics and time trends of HFMD, vaccination status and vaccine protection effect assessment of EV71 vaccine from 2011 to 2021 in Huangpu District, Shanghai, China. HFMD cases showed a decreasing trend year by year from 2011 to 2021, from 122 cases reported in 2012 to 7 cases in 2020, and 12 cases in 2021. Etiological diagnosis was CV-A6 in 185 cases (29.8%), CV-A16 in 209 cases (33.7%), EV-A71 in 118 cases (19.0%) and other enteroviruses in 109 cases (17.6%). After the launch of EV71 vaccine, a total of 32,221 doses of EV71 vaccine were administered between 2016 and 2021. The case-control results showed that there was no evidence to support the effectiveness of EV71 vaccine, OR (95% CI) =0.52 (0.12~2.3), p=0.37. The epidemic strains have changed. Surveillance and management of HFMD remain very important in the future and EV71 vaccine is considered to be included in National Immunization Program.